THU0331 Myeloperoxidase depletion is a selective feature of takayasu arteritis and predicts the clinical outcome. (15th June 2017) - Manfredi, AA; Ramirez, GA; Canti, V; Tombetti, E; Baldini, M; Baldisera, E; Rovere-Querini, P; Maugeri, N
Abstract : Background: Takayasu's arteritis (TA) is a rare large-vessel vasculitis characterized by persistent remodelling of the vessel walls. The role of innate immune cells in TA is poorly understood. Biomarkers to be used for assessment of TA activity and clinical outcome are missing. A trimodal pattern of myeloperoxidase (MPO) distribution (simultaneous occurrence of neutrophils with complete depletion, reduced and normal content of the enzyme) is detectable in the very early phase of acute myocardial infarction and has been associated with a burst of neutrophil interaction with activated platelets 1 Objectives: Here, we aimed at characterizing the phenotype of neutrophils and platelets in patients TA and correlating these biological findings with clinical data. Methods: neutrophil MPO expression has been studies in 93 subjects, including 21 TA patients, 20 age- and sex-matched healthy donors that served as controls, 25 patients with chronic stable atherosclerosis (CSA), eight patients with giant cell arteritis (GCA), five patients with gramulomatosis with polyangitis (GPA), four patients with eosinophilic GPA (EGPA) and ten patients with polymyalgia rheumatica (PMR). Blood samples were collected and processed as described 1–3 . Neutrophil MPO content, platelet P-selectin and High-Mobility Group B1 (HMGB1) in platelet derived microparticles (PDμP) release were assessed by flow cytometry. TA patients were then followed up for a median time of 3.43 years. Results: The trimodal distribution of neutrophils MPO content was identified in 17/21 TA, 1/8 GCA, 0/10 PMR, 0/25 CSA, 0/5 GPA and 0/4 EGPA patients; moreover in 0/20 healthy controls (ANOVA, F=15.22, p <0.0001). Neutrophil MPO content and the presence of neutrophils with complete MPO depletion in TA patients correlated inversely with i) platelet P-selectin expression (p<0.01), ii) the fraction of HMGB1 + -PDμP (p<0.01) and iii) disease duration, implicating an association of platelet and neutrophil activation with the disease natural history. In fact, the Kaplan Mayer analysis reveals that TA patients that had neutrophils with complete MPO depletion are at a significantly increased risk of ischemic complications during the follow up (long-rank=4.864, p=0.027, HR=36.15 abd CI-95%=0.15–7.51). Conclusions: Neutrophils and platelets are significantly activated in TA. Paroxysmal neutrophils activation, leading to complete MPO depletion, is a common feature and predict ischemic events and as such the clinical disease outcome. References: Maugeri N, Rovere-Querini P, Evangelista V, et al. An intense and short-lasting burst of neutrophil activation differentiates early acute myocardial infarction from systemic inflammatory syndromes. PLoS One 2012;7:e39484. Manfredi AA, Baldini M, Camera M, et al. Anti-TNFalpha agents curb platelet activation in patients with rheumatoid arthritis. Annals of the rheumatic diseases 2016;75:1511–20. Maugeri N, Campana L, Gavina M, et al. Activated platelets present high mobility group box 1 to neutrophils, inducing autophagy and promoting the extrusion of neutrophil extracellular traps. Journal of thrombosis and haemostasis: JTH 2014;12:2074–88. Disclosure of Interest: None declared